Histological and clinicoradiographic evaluation of desmoplastic ameloblastoma - Gupta, Shikha; Soni, Priyanka; Kapoor, Anjali; Vijay, Sharmishtha; Mathur, Setu; Soni, Shri R. (International Journal of Research in Medical Sciences, 2026)
A rare histologic variant of ameloblastoma, desmoplastic ameloblastoma is an odontogenic neoplasm that is challenging to diagnose. According to the case report, a 37-year-old female patient with history of intermittent pain and a hard swelling in the maxillary anterior region that measured 10×12 mm is discussed here. This variant frequently occurs in the anterior maxilla, despite the fact that ameloblastomas are typically found in the mandible. Following radiographic and clinical evaluation, surgical enucleation was carried out, and histopathological analysis was completed with the aid of H and E staining. In order to diagnose this uncommon form of ameloblastoma, we are attempting to shed light on the clinico-radiographic and histopathological features of desmoplastic ameloblastoma.